2021
DOI: 10.1038/s41419-021-03904-4
|View full text |Cite
|
Sign up to set email alerts
|

USP35, regulated by estrogen and AKT, promotes breast tumorigenesis by stabilizing and enhancing transcriptional activity of estrogen receptor α

Abstract: Although endocrine therapies targeting estrogen receptor α (ERα) are effective in managing ER positive (+) breast cancer, many patients have primary resistance or develop resistance to endocrine therapies. In addition, ER+ breast cancer with PIK3CA activating mutations and 11q13-14 amplification have poor survival with unclear mechanism. We uncovered that higher expression of deubiquitinase USP35, located in 11q14.1, was associated with ER+ breast cancer and poor survival. Estrogen enhanced USP35 protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Besides, deubiquitinase USP35 could restrain STING-mediated interferon signaling in ovarian cancer, highlighting the potential associations between USP35 and CD8 + T cell infiltrations [ 20 ]. Moreover, AKT-activated USP35 enhanced ERα stability by interacting and deubiquitinating ERα, suggesting that USP35 may be a therapeutical vulnerability for ER + breast cancer with endocrine resistance [ 21 ]. Considering USP35 correlates tightly with tumor progression, whether USP35 could modulate other oncogenic features, like metabolic remodeling, stem-like properties is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, deubiquitinase USP35 could restrain STING-mediated interferon signaling in ovarian cancer, highlighting the potential associations between USP35 and CD8 + T cell infiltrations [ 20 ]. Moreover, AKT-activated USP35 enhanced ERα stability by interacting and deubiquitinating ERα, suggesting that USP35 may be a therapeutical vulnerability for ER + breast cancer with endocrine resistance [ 21 ]. Considering USP35 correlates tightly with tumor progression, whether USP35 could modulate other oncogenic features, like metabolic remodeling, stem-like properties is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ERα has been shown to be a substrate of deubiquitinase (Pesiri et al, 2016). A few DUBs exert their pro-oncogenic function by triggering ERα deubiquitination to maintain the stability of ERα in BCa (Cao et al, 2021; Tang et al, 2021; Wang et al, 2020; Xia et al, 2021; Xia et al, 2019). Furthermore, DUB inhibitors targeting USP14 and UCHL5 downregulate ERα expression and induce cancer cell apoptosis, providing a prospective strategy for ER-positive BCa treatment (Xia et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation in USP35 seems to be not limited to HCC as other studies showed also upregulation of USP35 expression in lung, ovarian, colon adenocarcinoma, and head and neck cancer. USP35 is also involved in breast cancer progression by stabilizing and increasing transcriptional activity of estrogen receptors 35–37 …”
Section: Mitochondria‐attached Dubs Directly Involved In Mitophagymentioning
confidence: 99%
“…USP35 is also involved in breast cancer progression by stabilizing and increasing transcriptional activity of estrogen receptors. 35 , 36 , 37 …”
Section: Mitochondria‐attached Dubs Directly Involved In Mitophagymentioning
confidence: 99%